Acute disseminated toxoplasmosis in an immunocompetent adult patient. Case report - Juan Sebastián Frías-Ordoñez; Whendy Alejandra Mendoza-Acevedo; Johan Fernando Devia-Alvira; María Teresa Ospina-Cabrera; Pedro Pablo Osejo-Diago (Case Reports)
Abstract